Length-weight relationships, condition and population structure of the genus Atlantoraja (Elasmobranchii, Rajidae, Arhynchobatinae) in Southeastern Brazilian waters, SW Atlantic Ocean - Oddone, María Cristina [UNESP]; de Amorim, Alberto Ferreira (Northwest Atlantic Fisheries Organization (NAFO), 2007)
During the present study, 107 specimens of Atlantoraja castelnaui, 188 of A. platana, and 770 of A. cyclophora, were obtained by commercial vessels operating in Southeastern Brazil from March 2005 to April 2006. Males of A. castelnaui ranged from 17.9-111.0 cm and females from 17.4-116.0 cm total length. Males of A. platana ranged from 13.1-70.0 cm and females from 12.5-76.0 cm total length. Males of A. cyclophora ranged from 13.3-58.5 cm and females from 11.5-68.0 cm total length. Length-weight curves were sexually dimorphic in the three species. The analysis of the angular coefficient (b) demonstrated that growth (in weight) in relation to length was allometric (b>3) in males of A. castelnaui and A. platana, while isometric (b = 3) in females of these species. Conversely, growth of A. cyclphora was isometric in males, while in females it was allometric (b>3). The condition factor varied significantly throughout the year only in females of A. castelnaui.
Keywords: Angular coefficient; Condition factor; Elasmobranch; Morphometrics; Skates; commercial species; flatfish; growth rate; length-weight relationship; morphometry; population structure; sexual dimorphism; Atlantic Ocean; Brazil; South America; Arhynchobatinae; Atlantoraja; Atlantoraja castelnaui; Atlantoraja cyclophora; Atlantoraja platana; Elasmobranchii; Rajidae